An Analysis of Antihero in Markus Zusak’s I am the Messenger - Sri Maryani (Passage, 2017)
In order to explore the presentation of antihero in Markus Zusak’s I am the Messenger, this study uses Roberts and Jacobs’ (2004) theory on methods of characterization and Brombert’s (1999) and Wilson’s (2013) characteristics of antihero. With the aim of achieving an understanding of the characterization of antihero, this study employs a qualitative method which focuses on the main character’s characteristics, Ed Kennedy. The characteristics of antihero shown through four elements of characterization: environment, appearance, actions, and speech. According to his environment, Ed is characterized as a teenager who has an unhappy life because he belongs to the low economic status. Second, his appearance does not present that he is a protagonist in the novel. Third, he acts like a hero, especially in helping the other characters. Finally, the other characters perceive that he is weak and doubtful. On the other hand, he is an obedient and empathetic person. From the analysis, it can be concluded that he has two different characteristics which are good and bad. Some certain events were constructing him to be a better person. In the beginning of the story, he is only a weak and doubtful person. As the story goes by, he changes; he enforces to feel the fear and empathy.Keywords: antihero; character; characterization